TAFSIR SYI’AH SEBAGAI DAKHIL: KAJIAN KRITIK HUSEIN AL-DHAHABI ATAS TAFSIR FATH AL-QADIR - Riyadi, Ahmad Agus Salim dan Abdul Qodir (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2022)
After the development of Islamic dominion, the Ahlul Kitab (the Tabi'in Period) who knew the stories of the prophets and previous peoples entered Islam. However, the Qur'an in discussing the stories is only brief and not in detail. However, everyone must have a tendency to be complete and detailed, and listen to these stories in detail and make them a reference in interpreting the Qur'an. Thus causing controversy among scholars whether the stories of Israel can be used in interpretation or not. Related to this, the scholars have sparked the latest scientific disciplines in order to protect the interpretation from errors and deviations from it, namely the science of al-Asil and al-Dakhi>l which emerged in 1980 AD. al-Qur'an from faulty thinking or wrong logic, or commonly called al-Dakhi>l fi al-Ra'yi into seven kinds. In this article, we only discuss one of them, namely al-Dakhi>l from the path of heretical schools in Islam, especially Huseyn al-Zahaby's criticism of the interpretation of the Zaydiyyah Shia group in the interpretation of Fath al-Qadir. The following are his criticisms, namely, first, against the Mawdu>' (False) and Dhaif (weak) narrations, and he did not give any comment on these narrations. Second, on the interpretation of al-Shawkani in the story of the Prophet Yusuf and Zulaikha, especially the temptation made by al-Aziz's wife against the Prophet Yusuf. Third, to the Mutasa>bih verses interpreted by al-Shawkani, which he mentions in lafaz-lafaz in the Qur'an. Fourth, to al-Shawkani's view on the issue of the Qur'an is makhluq.